Pharmaceutical technological aspects and possibility of using transdermal patches in paediatric population - Đekić Ljiljana; Živković Sanja; Primorac Marija (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
The administration of drugs via skin to achieve systemic effects is simple and noninvasive, and thus represents a more suitable alternative for pediatric population when compared with per os and parenteral routes. This pharmaceutical dosage form provides a controlled drug release and subsequent reduction in the frequency of administration and increased patient adherence. In 2006, the Food and Drug Administration (FDA) approved the use of a transdermal patch with methylphenidate, which is designed for the pediatric population. Transdermal patches with an opioid analgesic (fentanyl, buprenorphine), clonidine, scopolamine, tulobuterol, estrogens and nicotine, have been developed for use by adult patients, and have been registered for the use in children of a certain age, and/or the literature described the clinical studies or examples in practice of their off label use with respect to the age of the patient, the dose and/or indications. The Regulation (EC) 1901/2006 on medicinal products for paediatric use and the Guideline on pharmaceutical development of medicines for pediatric use EMA/CHMP/QWP/805880/2012 pointed out that design of transdermal patches requires careful consideration of: specificities in development and the variation of the skin barrier function, the choice of excipients with consideration of their potential for irritation or sensitization of the skin, the range of the quantity of drug which is released per unit of time and the surface on which the drug release is performed (as well as the overal size of a transdermal patch), which should be adequate to meet the individual therapeutic needs of children of different ages.